Professional Development of New Higher Education Teachers With Information and Communication Technology in Shanghai: A Kirkpatrick's Evaluation Approach. (July 2016) - Wu, Bian; Hu, Yiling; Gu, Xiaoqing; Lim, Cher Ping
As information and communication technology (ICT) continues to develop, it is essential for teachers to acquire ability for teaching with ICT. In China, new higher education (HE) teachers often lack teaching experience because there are limited teaching opportunities during their postgraduate studies. This status quo may compromise the quality of teaching and learning in higher education institutions. In 2013, Shanghai Municipal Education Commission initiated a professional development program for new teachers from all local higher education institutions. This article examines their ICT professional development through the lens of Kirkpatrick's evaluation model. Data were collected from online surveys both immediately after an ICT module and 6 months later. The results showed that participants intended to integrate ICT in teaching and had an above-average level of Technological Pedagogical and Content Knowledge (TPACK). Participants and their department heads also confirmed distinctive teaching performance of these new teachers and better learning behavior of their students. The study revealed that demographic variables of new HE teachers may also affect their perception of ICT and TPACK. This study suggests that ICT professional development can have positive impacts on new HE teachers' perception of ICT, their TPACK competence, and ICT-related teaching practice and student learning.